Proportional assist and neurally adjusted ventilation: Clinical knowledge and future trials in newborn infants. Issue 7 (15th March 2021) - Sindelar, Richard; McKinney, Robin L.; Wallström, Linda; Keszler, Martin
Abstract: Different types of patient triggered ventilator modes have become the mainstay of ventilation in term and preterm newborn infants. Maintaining spontaneous breathing has allowed for earlier weaning and the additive effects of respiratory efforts combined with pre‐set mechanical inflations have reduced mean airway pressures, both of which are important components in trying to avoid lung injury and promote normal lung development. New sophisticated modes of assisted ventilation have been developed during the last decades where the control of ventilator support is turned over to the patient. The ventilator detects the respiratory effort and adjusts ventilatory assistance proportionally to each phase of the respiratory cycle, thus enabling the patient to have full control of the start, the duration and the amount of ventilatory assistance. In this paper we will review the literature on the ventilatory modes of proportional assist ventilation and neurally adjusted ventilatory assistance, examine the different ways the signals are analyzed, propose future studies, and suggest ways to apply these modes in the clinical environment.